The effects of international acquisitions in Serbia on status and engagement of human resources - Rakita, Branko; Marković, Dušan (Industrija, 2013)
In the past few decades globalization and deregulation of international economy has been noticeably accelerated. Consequently, new globalized business environment with numerous business opportunities as well as growing business risks has been made. The new business environment opened the door to intensive implementation of acquisitions as a market entry strategy. Foreign direct investments (FDI) in most of transition countries, including Serbia, predominantly come in the form of international acquisitions. There is a wide theoretical analysis of the effects of FDIs on target country economy. The overall conclusion is that green field projects, in comparison with international acquisitions, have more favorable effects on all aspects of host country’s economy. This paper examines the effects of international acquisitions in Serbia on work practices, wages and productivity using the analysis of the financial statements and the results of survey carried out among the foreign investors. It was found that decline of employment; productivity growth and increase in real wages are the results of the acquisitions. The survey also shows that the foreign investors invested in training and development of the acquired employees.